Quantitative Analysis of Superb Microvascular Imaging versus Color-Coded Doppler Sonography for Preoperative Evaluation of Vascularization of Schwannomas - Kloth, Christopher; Eissler, Alexandra; Schmidberger, Julian; Gräter, Tillmann; Scheuerle, Angelika; Kratzer, Wolfgang; Pedro, Maria Teresa (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Purpose Comparison of vascularization of schwannomas, benign peripheral nerve sheath tumors, using color-coded Doppler sonography (CCDS) and the Toshiba monochrome Superb Microvascular Imaging (mSMI) (Minato, Tokyo, Japan) technique.Methods In a retrospective single-center analysis, 16 patients were identified with histologically confirmed schwannomas. Between March and June 2018, all of them underwent ultrasonography using mSMI and CCDS before surgery. Schwannoma vascularization was quantitatively measured using ImageJ, an open platform for scientific image analysis. As the diagnostic gold standard, magnetic resonance imaging was mandatory.Results The mSMI and CCDS vascularization showed a moderate agreement between the techniques (κ = 0.5556; p = 0.0066). The quantitative visual assessment of the vascularization revealed no difference (25.3 ± 8.2 vs. 18.2 ± 3.8; p = 0.0532). Significant differences were found for the quantitative assessment of CCDS with ImageJ (26.8 ± 8.8 vs. 19.3 ± 2.8; p = 0.0368). However, in a subanalysis of highly vascularized schwannomas, mSMI revealed significant differences to slightly vascularized schwannomas (32.0 ± 8.2 vs. 21.3 ± 6.1; p = 0.0065) but not between moderately and slightly vascularized types (p = not significant).Conclusion The mSMI mode is qualitatively superior to conventional CCDS; however, quantitative analysis of the vascularization of schwannomas revealed no significant quantitative advantage for mSMI. Nevertheless, the mean ImageJ values showed a positive trend toward a better representation of the vascularization degree of schwannomas with mSMI.
Keywords: schwannoma; neurosonography; monochrome Superb Microvascular Imaging; benign peripheral nerve sheath tumor